The Study of the Specific Activity of the Gel Containing Chitosan-Myramistin-Chymopsin Complex on the Linear and Planar Wounds’ Model - Brkich, Galina Eduardovna (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The objective of the study was to assess the reparative and antibacterial properties of the gel containing chitosan-myramistin-chymopsin on the model of the linear and planar wounds in rats. Materials and Methods: Histological study has been performed on the material of the cutaneous flaps sized 1.5 x 1.0 x 0.5 cm, stained with eosin, from 48 animals divided into 6 groups: 8 rats with linear wound treated with CMCC-based gel (LWG), 8 rats with planar wound treated with test gel (PWG), 8 rats with planar wound and comparator agent (PWCA), 8 rats with linear wound and comparator agent (LWCA). The animals were withdrawn from the experiment, and the material was taken on the 8th day in case of the linear wound and on the 35th day in case of planar one. Results: The wound healing-reparation degree was assessed by the following morphological features: The presence/absence of the wound canal and necrosis, granulation tissue and its maturity, epithelialization, inflammatory response and the nature of the inflammatory infiltrate (leucocytic, lymphoid, macrophagal), as well as the changes in the extracellular matrix or fibrosis severity. Conclusion: Thus, based on reparation signs, the more effective tissue reparation had been observed in groups with gel, comparator agent and PWR, the least effective - in the LWR group, which was probably due to the accession of secondary infection and festering development. In the groups treated with gel and comparator agent the average reparation level had been revealed, and in case of the linear wound the gel proved to be more effective, compared to the comparator agent, and in planar wounds’ group the level of reparation was equally high.